Innovative Pedagogical Technologies in Education System - Mexro’zbek Muxtorjon o’g’li Jo’raboyev; Yuldasheva Shaxnoza Maxmudovna (Scientific Trends, 2023)
The society in which we live is constantly evolving and changing. The modern world educational space is constantly being replenished with new content of knowledge, new qualifications. New spheres of relations are emerging, new specialties that form new disciplines. World higher education is undergoing reform. This led to the search for new forms and technologies of education. Harmonization of higher education in accordance with the requirements of the world space and standards, its development is carried out according to certain principles. This is, first of all, the priority introduction of innovative achievements in education and science. It is known that it is the innovative way of development of society that can ensure the formation of a generation of people who think and work in a new way. As a result, the main attention will be paid to the development of personality, cultural and communicative preparedness, the ability to independently acquire and develop knowledge, to form information and social skills. Considering this, the main purpose of the article is to study the main aspects of innovative pedagogical technologies in education system.
Keywords: Higher education, Innovative achievements, Pedagogical technologies, Pedagogy.